Pengaruh Belajar Sosial Terhadap Penyalahgunaan Alkohol Oleh Remaja - Asriyani M Arifin (IAIN TERNATE, 2022)
This research is qualitative research with survey methods. The research was conducted at a high school in the City of Tidore Islands. The subjects of the study were 100 respondents. Based on the results of data analysis using SPSS with the Rank-order correlation technique (Sprearman's Rho Rank-order Correlation), a correlation coefficient value of 0.854 was obtained. The conclusion of the study is that social learning variables have a relationship with alcohol abuse. The value of the positive correlation coefficient indicates a positive relationship direction, namely that the higher the level of social learning, the higher the level of alcohol abuse, and vice versa. For this reason, social learning variables are variables that affect alcohol abuse. For this reason, it is necessary to take preventive measures so that adolescents do not fall into alcohol abuse behavior. Parental supervision of adolescent associations is important to prevent children from falling into alcohol abuse behavior.